2016
DOI: 10.1007/s00216-016-9716-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of coverage, retention patterns, and selectivity of seven liquid chromatographic methods for metabolomics

Abstract: Liquid chromatography-mass spectrometry (LC-MS)-based metabolomics studies require highly selective and efficient chromatographic techniques. Typically employed reversed-phase (RP) methods fail to target polar metabolites but the introduction of hydrophilic interaction liquid chromatography (HILIC) is slow due to perceived issues of reproducibility and ruggedness and a limited understanding of the complex retention mechanisms. In this study, we present a comparison of the chromatographic performance of a tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…101 In another comprehensive study, the chromatographic performance of RPLC, zwitterionic, amide-, alkyl diol-, and aminoalkyl-based HILIC and RP/ HILIC MMC on 714 metabolite standards and human plasma was compared. 124 Only 37% of the metabolite standards displayed good peak shape and good retention (retention factor k > 1) on RPLC, and as expected, a combination of MMC or HILIC with RPLC could expand the coverage up to 52-66% of the standards. Because the combination of different chromatography methods could increase metabolome coverage, MDLC approaches, which have been commonly adopted in proteomics, are also of interest in metabolomics.…”
Section: Expand Metabolome Detection Via Different Types Of Liquid supporting
confidence: 62%
See 1 more Smart Citation
“…101 In another comprehensive study, the chromatographic performance of RPLC, zwitterionic, amide-, alkyl diol-, and aminoalkyl-based HILIC and RP/ HILIC MMC on 714 metabolite standards and human plasma was compared. 124 Only 37% of the metabolite standards displayed good peak shape and good retention (retention factor k > 1) on RPLC, and as expected, a combination of MMC or HILIC with RPLC could expand the coverage up to 52-66% of the standards. Because the combination of different chromatography methods could increase metabolome coverage, MDLC approaches, which have been commonly adopted in proteomics, are also of interest in metabolomics.…”
Section: Expand Metabolome Detection Via Different Types Of Liquid supporting
confidence: 62%
“…Although ANP performed better in the analysis of polar metabolite standards compared to RPLC (80% of the standards eluted in the solvent front in RPLC), zwitterionic HILIC showed the best chromatographic performance and the greatest coverage for the metabolite standards and polar metabolites in urine . In another comprehensive study, the chromatographic performance of RPLC, zwitterionic, amide‐, alkyl diol‐, and aminoalkyl‐based HILIC and RP/HILIC MMC on 714 metabolite standards and human plasma was compared . Only 37% of the metabolite standards displayed good peak shape and good retention (retention factor k > 1) on RPLC, and as expected, a combination of MMC or HILIC with RPLC could expand the coverage up to 52‐66% of the standards.…”
Section: Metabolome Coverage Expansionmentioning
confidence: 99%
“…Several previous studies have focused on metabolome coverage, peak capacity, and overall performance of different columns suitable for LC‐based metabolomics applications . For example, in the study of Wernisch et al., the comparison focused on investigation of metabolome coverage, retention time profile, peak shape, and selectivity from different hydrophilic interaction liquid chromatography (HILIC) columns . Walles et al.…”
Section: Introductionmentioning
confidence: 99%
“…RPLC remains the most popular mode of HPLC for practical broad scale metabolome coverage as the retention characteristics of these materials are well-suited to a range of moderately polar and nonpolar Several previous studies have focused on metabolome coverage, peak capacity, and overall performance of different columns suitable for LC-based metabolomics applications [10]. For example, in the study of Wernisch et al, the comparison focused on investigation of metabolome coverage, retention time profile, peak shape, and selectivity from different hydrophilic interaction liquid chromatography (HILIC) columns [11]. Walles et al also compared separation efficiency and precision of two metabolites: norverapamil and o-demethylverapamil in human-liver microsomal incubates analysis on two sub-2 m particle columns, with results indicating that there was no substantial improvement when changing from 1.8 m to 1.7 m particle size [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comparison of the chromatographic performance of a traditional ODS column with various HILIC and mixed-mode columns showed that ODS and zwitterionic HILIC columns are the best combination for wide metabolite coverage. 51) e poor quality control and incompatibilities among the data acquisition procedures seriously hamper meta-analysis of biomarkers using metabolome datasets.…”
Section: Bottleneck In the Metabolomics 2: Quantification Without Valmentioning
confidence: 99%